PENGARUH PENYAJIAN LAPORAN KEUANGAN DAERAH DAN AKSESIBILITAS LAPORAN KEUANGAN DAERAH TERHADAP TRANSPARANSI DAN AKUNTABILITAS PENGELOLAAN KEUANGAN (KOTA MALANG DAN KABUPATEN MALANG ) - Mardhani Susilawati; Anik Malikah; M. Cholid Mawardi (Universitas Islam Malang, 2022)
This research was conducted to analyze “the influence of the presentation of regional financial statements and the accessibility of regional financial statements on the transparency and accountability of regional financial management in Malang City and Malang Regency”. The sample in this study were active employees of the Malang city and district government as users of financial reports presented by local governments, in accordance with applicable laws and regulations. The municipal government employees who are the respondents are the Budget and Treasury Division, Accounting and Regional Asset Management Division and Regional Asset Utilization Division and have worked for more than 1 year. The analytical method used is Multiple Linear Regression with SPSS 22 Software For Windows. Based on the results of the hypothesis test that simultaneously Presentation of Regional Financial Statements and Accessibility of Regional Financial Statements have a positive and significant effect on Transparency & Accountability of Regional Financial Management in Malang City and Malang Regency. Partially, it shows that the Presentation of Regional Financial Statements and Accessibility of Regional Financial Statements have a positive and significant effect on Transparency & Accountability of Regional Financial Management in Malang City and Malang Regency.Keywords: Presentation of Regional Financial Reports, Accessibility of Regional Financial Reports, Transparency & Accountability of Regional Financial Management